Massive timber building vs. conventional masonry building. A comparative life cycle assessment of an Italian case study. (August 2019) - Pittau, F; Dotelli, G; Arrigoni, A; Habert, G; Iannaccone, G
Abstract: This work aims to investigate the environmental friendliness of building materials, and in particular the benefit of using biogenic products as replacement of conventional materials. The sustainability of wood as a construction material is a complex issue since the environmental impacts are strongly related to forest management, service life and, finally, to end-of-life scenarios and waste treatment processes. In this study, a Life Cycle Assessment (LCA) comparison was carried out between a semi-detached house out of cross-laminated timber (CLT) and a conventional building with similar geometric characteristics and equal thermal performance (U-value), out of light-clay bricks with a reinforced concrete structure. Particularly, the environmental impacts from raw materials supply, transportation and product processing (cradle to gate) were investigated and the Recipe mid-point method was adopted for the impact assessment to compare the environmental burdens of the two equivalent buildings. The positive environmental values resulted in the massive timber building are mainly connected to the replacement of the reinforced concrete mass used in the structure. The outcome, in terms of global warming potential, show that the use of wood as a building material instead of conventional materials results in a reduction of greenhouse gas emissions of roughly 25%. This material replacement, if extended on a large scale, could give a valid contribution on achieving the community goals of reducing emissions from the construction sector.